Circulating essential metals and lung cancer: Risk assessment and potential molecular effects. (June 2019) - Bai, Yansen; Wang, Gege; Fu, Wenshan; Lu, Yanjun; Wei, Wei; Chen, Weilin; Wu, Xiulong; Meng, Hua; Feng, Yue; Liu, Yuhang; Li, Guyanan; Wang, Suhan; et al.
Abstract: Objective: Essential metals play important roles in the carcinogenic process. However, seldom longitudinal investigations have evaluated their roles in lung cancer development. We aimed to investigate the associations between multiple essential metals and lung cancer incidence and to explore the potential mechanisms. Methods: A nested case-control study of 440 incident lung cancer cases and 1:3 frequency matched 1320 healthy controls from the Dongfeng-Tongji Cohort was conducted. The baseline plasma concentrations of 11 essential metals (cobalt, copper, iron, manganese, molybdenum, rubidium, selenium, strontium, stannum, vanadium, and zinc) were measured, and their associations with lung cancer incidence were estimated. Effect of positive metal (zinc) on 4-year telomere attrition was then evaluated among an occupational cohort of 724 workers. We also assessed the transcriptional regulation effects of plasma zinc on mRNA expression profiles, and the expressions of zinc-related genes were further compared in pair-wised lung tumor and normal tissues. Results: Elevated plasma level of zinc was associated with lower incident risk of lung cancer [OR (95% CI) = 0.89 (0.79, 0.99)] and decreased 4-year telomere attrition [β (95% CI) = −0.73 (−1.27, −0.19)]. These effects were pronounced among males. In particularly, zinc could regulate the expressions of 8 cancer-related genes, including SOD1, APE, TP53BP1, WDR33, LAPTM4B, TRIT1, HUWE1, and ZNF813, which were over-expressed in lung tumor tissues. Conclusions: We propose that high plasma zinc could prevent incident lung cancer, probably by slowing down telomere attrition and regulating the expressions of cancer-related genes. These results provided a new insight into lung cancer prevention. Highlights: Increased plasma zinc level was associated with a lower risk of lung cancer. High plasma zinc level was associated with decreased telomere length attrition. Plasma zinc level was associated with the expressions of 13 cancer-related genes. 8 of the 13 cancer-related genes were up-regulated in lung tumor tissues.